2018
DOI: 10.1016/j.htct.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of receptor for hyaluronan acid-mediated motility (CD168) in acute pediatric leukemias – assessment of clinical outcome, post induction, end of treatment and minimal residual disease

Abstract: IntroductionThe extracellular matrix protein hyaluronan acid plays an active in role in tumor cell proliferation and invasion. Hyaluronan acid receptors, namely CD168 or the receptor for hyaluronan acid-mediated motility (RHAMM) and CD44 have been implicated in promoting malignancy. There is a lacuna in data on the expression of the receptor in pediatric leukemias.MethodsPediatric patients with acute leukemia who were diagnosed, treated and followed up in our center were enrolled. The bone marrow biopsies perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…CD168 or receptor for hyaluronan-mediated motility (RHAMM) was described as widely expressed LAA in AML, CML, and CLL [128,129]. A possible role of RHAMM as a biomarker for patient prognosis in acute pediatric leukemias was investigated revealing that patients with a high percentage of RHAMM-positive blast cells at the time of diagnosis had more blasts in minimal residual disease and a poorer prognosis [130]. By the in silico prediction of potential HLA-A*02-presented peptides from RHAMM, the peptide R3 (ILSLELMKL) was first characterized as a highly immunogenic CD8 + T-cell epitope in AML patients [83].…”
Section: Hla-dependent Antigensmentioning
confidence: 99%
“…CD168 or receptor for hyaluronan-mediated motility (RHAMM) was described as widely expressed LAA in AML, CML, and CLL [128,129]. A possible role of RHAMM as a biomarker for patient prognosis in acute pediatric leukemias was investigated revealing that patients with a high percentage of RHAMM-positive blast cells at the time of diagnosis had more blasts in minimal residual disease and a poorer prognosis [130]. By the in silico prediction of potential HLA-A*02-presented peptides from RHAMM, the peptide R3 (ILSLELMKL) was first characterized as a highly immunogenic CD8 + T-cell epitope in AML patients [83].…”
Section: Hla-dependent Antigensmentioning
confidence: 99%
“…58 In patients with acute leukemia, the expression of RHAMM correlates with minimal residual disease and worse survival. 59 According to the results of Schütze and Wang, it is suggested that RHAMM has an important role in the invasiveness of tumor cells. Suggesting that due to its role in invasion RHAMM is a poor prognostic factor for patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in multiple myeloma, the expression of RHAMM was also associated with poor survival and osteolytic bone lesions 58 . In patients with acute leukemia, the expression of RHAMM correlates with minimal residual disease and worse survival 59 . According to the results of Schütze and Wang, it is suggested that RHAMM has an important role in the invasiveness of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-cancer immune responses: in-depth exploration have led to the classification of NSCLC, specifically lung squamous carcinoma (LUSC), as an "immunotherapyresponsive disease" [109]. Mutations affecting cellular iron levels within tumor cells have the potential to trigger robust anti-tumor immune responses both in vivo and in vitro, thereby potentially enhancing the efficacy of immune checkpoint inhibitors [110].…”
Section: Beas-2b Cellsmentioning
confidence: 99%